The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep14999
|View full text |Cite
|
Sign up to set email alerts
|

Bursts of Bipolar Microsecond Pulses Inhibit Tumor Growth

Abstract: Irreversible electroporation (IRE) is an emerging focal therapy which is demonstrating utility in the treatment of unresectable tumors where thermal ablation techniques are contraindicated. IRE uses ultra-short duration, high-intensity monopolar pulsed electric fields to permanently disrupt cell membranes within a well-defined volume. Though preliminary clinical results for IRE are promising, implementing IRE can be challenging due to the heterogeneous nature of tumor tissue and the unintended induction of mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 53 publications
3
87
0
Order By: Relevance
“…applications that utilize controlled, square electrical pulses on the order of one microsecond [19,58]. The observations about PEFs with single-microsecond pulse widths from the field of PEF-based food processing do not directly provide information on the efficiency of these pulses to enhance molecular transport across mammalian cell membranes.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…applications that utilize controlled, square electrical pulses on the order of one microsecond [19,58]. The observations about PEFs with single-microsecond pulse widths from the field of PEF-based food processing do not directly provide information on the efficiency of these pulses to enhance molecular transport across mammalian cell membranes.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…estimates When PI binds to nucleic acids, it undergoes a dramatic fluorescence increase, making it useful in assays for evaluating membrane integrity, such as cell death [19] or membrane permeabilization [67,66], which rely on a binary result. Continuous measurements have been performed [65] using chemical agents to calibrate fluorescence intensity measurements, though they have not been used to study the temporal evolution of membrane permeability induced by electric fields with pulse widths on the order of the characteristic membrane charging time.…”
Section: Objective Analysis Of Different Electroporation Protocols Mamentioning
confidence: 99%
See 1 more Smart Citation
“…S10 and S11). It has been previously observed that H-FIRE treatment generates more homogenous lesions (2,24,(27)(28)(29)(30)(31) and in this article, we offer an explanation for that phenomenon.…”
Section: Figurementioning
confidence: 86%
“…The cell-killing effects of H-FIRE were later explored using 3D in vitro tumor constructs and in vivo subcutaneous murine tumors over a wide range of pulse durations (250 ns-100 µs) (41). The in vitro tumor constructs were assembled by mixing murine pancreatic tumor cells with collagen I hydrogel, injecting into cylindrical molds, and polymerizing at 37°C (42); the in vivo subcutaneous tumors were produced by injecting human GBM cells (DBTRG-05MG) into the dorsolateral flank region of athymic nude-Foxn1 nu mice.…”
Section: High-frequency Irreversible Electroporationmentioning
confidence: 99%